Natalizumab-associated progressive multifocal leukoencephalopathy - Glenn, Trevor; Berger, Joseph R.; McEntire, Caleb R. S. (Frontiers in Neurology, 2025)
Progressive multifocal leukoencephalopathy (PML) is a demyelinating disease of the brain resulting from infection of oligodendrocytes by JC virus (JCV) typically occurring in association with defects of cell-mediated immunity. The clinical presentation of PML depends on its area of effect in the central nervous system and can include a broad spectrum of deficits such as focal weakness, speech difficulties, visual changes, cognitive disruptions, or ataxia. While the disease was first described in patients with B cell malignancies (Hodgkins’s lymphoma and chronic lymphocytic leukemia), a large array of immunosuppressive conditions, most notably human immunodeficiency virus, may predispose to the disorder. From 2005 on, PML was observed in patients with multiple sclerosis (MS) and Crohn’s disease being treated with natalizumab, a monoclonal antibody inhibiting α4β1 and α4β7 integrins. Risk factors for PML development were identified, and an effective risk mitigation strategy chiefly predicated on the JCV antibody index was established (an antibody index less than 0.4 is considered negative, 0.4 to 0.9 low risk, 0.9 to 1.5 medium risk, and greater than 1.5 high risk). Here we review risk stratification, diagnosis, and treatment of PML in patients receiving natalizumab.